Public intent proﬁle towards medical facility visualisation systems in russian federation: a one-stage sociological survey - A. A. Kurmangulov; Yu. S. Reshetnikova (Кубанский научный медицинский вестник, 2021)
Background. Medical facility visualisation systems comprise navigation, information panels and visual operation control elements. Visual perception surveys in medical institutions are of great value in medical sociology. Knowing the today’s visitor intent towards visual content inside healthcare facilities will allow a better formulation of most comfortable arrangement of medical services and improvement of healthcare delivery to various visitor categories.Objectives. An assessment of modern public intent towards medical visualisation systems in the Russian Federation.Methods. A total of 7,356 citizens across 85 country subjects contributed to a sociological survey. Data of a formalised multistage stratified territorial random sampling survey were taken as main information source. The Kano model was used to organise intent towards attributes of medical visualisation systems. Depending on two parameters (functionality and satisfaction), the attributes were assigned between the categories of attractive, linear, obligatory, indifferent or undesirable.Results. The highest approval level among the visualisation attributes was found towards accuracy of the information panel content. The high-level of respondent approval were external navigation, compliance to the Russian language style and rules, good-making of the element, content structuring and use of modern information technologies. The lowest approval level was in a visually unified medical institution design. The most contentious respondent intent was observed in relation to colour-coding of visualisation objects.Conclusion. The survey recovered a generally similar public intent profile towards main visualisation system attributes in the Russian Federation. The mandatory included two attributes, “compliance to the Russian language style and rules” and “good-making of visualisation element”. Mandatory attributes are baseline to medical visualisation systems. They do not improve the visitor’s satisfaction, but their absence negatively impacts perception of healthcare visualisation systems.